2014
DOI: 10.1080/13607863.2014.967173
|View full text |Cite
|
Sign up to set email alerts
|

Why is dementia different? Medical students' views about deceiving people with dementia

Abstract: Dementia adds additional complexity to clinical judgements about the acceptability of deception in practice. Medical students have a number of unmet learning needs with regard to communicating with patients with dementia and their families. Existing ethical frameworks may provide a helpful starting point for education about dementia care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The uncertainty expressed by students about being able to be completely honest with PLWD at all times is reflected by literature on the ethics of lying and deception in dementia care. Whilst a minority of ethical discourse maintains a deontological view that lying in clinical practice is never acceptable (Bakhurst, 1992; Jackson, 2001), student opinion emerging from this study – that there are rare and specific circumstances where lying might be justifiable is congruent with research studies demonstrating that ‘white lies’ and deception do occur in dementia care (Elvish, James, & Milne, 2010; Hasselkus, 1997; Hertogh, The, Miesen, & Eefsting, 2004; Tuckett, 2012; Tullo, Lee, Robinson, & Allan, 2015). As per the diversity reflected in this literature as to which circumstances might be justifiable, students were similarly divided in their opinions.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The uncertainty expressed by students about being able to be completely honest with PLWD at all times is reflected by literature on the ethics of lying and deception in dementia care. Whilst a minority of ethical discourse maintains a deontological view that lying in clinical practice is never acceptable (Bakhurst, 1992; Jackson, 2001), student opinion emerging from this study – that there are rare and specific circumstances where lying might be justifiable is congruent with research studies demonstrating that ‘white lies’ and deception do occur in dementia care (Elvish, James, & Milne, 2010; Hasselkus, 1997; Hertogh, The, Miesen, & Eefsting, 2004; Tuckett, 2012; Tullo, Lee, Robinson, & Allan, 2015). As per the diversity reflected in this literature as to which circumstances might be justifiable, students were similarly divided in their opinions.…”
Section: Discussionsupporting
confidence: 55%
“…The author(s) declared the following potential conflicts of interest with respect to the research, authorship, and/or publication of this article: An article reporting on early data collection and analysis from the same research project, with an emphasis on cross-cultural analysis, has been published as a book chapter (Young, T. J., Tullo, E., & Lee, R. (2015). Person-centredness, culture and communication in dementia care: Attitudes among medical students.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Seaman and Stone (2017) highlight the complexities of deception in the context of dementia, noting that caring for people living with dementia involves dynamic interactions among a network of care providers, across various different settings. Collaborative, shared decision-making regarding the best interest of the person living with dementia is therefore critical (Tullo et al, 2015;Turner et al, 2017). In this way all key stakeholders are involved and are aware of the decision made regarding lying promoting consistency in approach (James & Caiazza, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of health care professionals, some writers highlight the need to better prepare and train health care professionals to communicate more effectively with people living with dementia (Tullo, Lee, Robinson, & Allan, 2015) and the importance of using collaborative interprofessional decision making (Turner et al., 2017). However, training for informal/unpaid carers as to how best respond when the person with dementia makes statements which are incorrect appears to be somewhat lacking, none of the informal/unpaid carers in our study reported receiving such training.…”
Section: Discussionmentioning
confidence: 99%
“…While the question of whether people with a probable dementia should be told their diagnosis has largely receded from the academic literature and current western health care practice, there is great nuance and variability in how the diagnostic process proceeds, bearing in mind variations in individuals' cognitive and communicative abilities, degree of insight, and (potential) co-morbidities. Recent research using focus groups and interviews with current medical students, for example, highlights that deception remains a live issue in the context of dementia health care and that issues of capacity, perceived vulnerability and family dynamics all complicate clinical judgments in the dementia care context (Tullo et al, 2015); and this likely impacts on clinical communication.…”
Section: Diagnostic Disclosurementioning
confidence: 99%